Literary Exploration of Women by Bharti Mukherjee in Desirable Daughters: Unveiling Women's Identities in Bharti Mukherjee's Desirable Daughters (Journal of Advances and Scholarly Researches in Allied Education, 2019)
India has a strong voice in the world of literature through the writers. The women writers have achieved distinctions through their writing by voicing out the concerns of a woman to create her identity in a male dominated society. One can see immense possibility of literary exploration in the work of Bharti Mukherjee who acclaimed internationally.